Research on damage viscoelastic dynamic constitutive model of granite - Ling Tianlong; Liu Dianshu; Liang Shufeng; Li Shenglin (矿业科学学报, 2019)
Dynamic mechanical properties of granite were tested by a split Hopkinson pressure bar system with constant strain rate.The initial loading stage of stress-strain curve of granite is linear elasticity, and the rock material has a significant plastic deformation after yielding.Yield strength, peak strength and elastic modulus are all rate dependent.Based on dynamic mechanical property of granite, the constitutive of Zhu-Wang-Tang model was simplified to apply on granite, and with consideration of the effect of damage on the dynamic strength of granite under impact load.The experimental data were fitted to the proposed model.The fitted stress-strain curves at different strain rates are in good agreement with the experimental ones.This demonstrates that the proposed dynamic constitutive model in this paper can accurately describe the dynamic mechanical properties of granite under the impact load.